2020
DOI: 10.1155/2020/1720961
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-1β Protects the Rat Diaphragm during Sepsis against Oxidative Stress and Inflammation by Activating the PI3K/Akt Pathway

Abstract: Sepsis-induced diaphragm dysfunction (SIDD) which is mainly characterized by decrease in diaphragmatic contractility has been identified to cause great harms to patients. Therefore, there is an important and pressing need to find effective treatments for improving SIDD. In addition, acetylcholinesterase (AChE) activity is a vital property of the diaphragm, so we evaluated both diaphragmatic contractility and AChE activity. Though neuregulin-1β (NRG-1β) is known to exert organ-protective effects in some inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The PI3K (phosphatidylinositol-3-kinase) pathway is a crucial signaling pathway in the body, and it maintains tissue homeostasis by regulating protein phosphorylation, methylation, and ubiquitination [ 44 ]. In sepsis, activation of the PI3K pathway can reduce damage to the diaphragm [ 46 ], myocardium [ 47 ], lung [ 48 ], and other tissues and organs by inhibiting the degradation of I κ B α . Mitogen-activated protein kinase (MAPK) is an essential member of the intracellular signaling protein network that mediates extracellular stimuli to intracellular responses.…”
Section: Resultsmentioning
confidence: 99%
“…The PI3K (phosphatidylinositol-3-kinase) pathway is a crucial signaling pathway in the body, and it maintains tissue homeostasis by regulating protein phosphorylation, methylation, and ubiquitination [ 44 ]. In sepsis, activation of the PI3K pathway can reduce damage to the diaphragm [ 46 ], myocardium [ 47 ], lung [ 48 ], and other tissues and organs by inhibiting the degradation of I κ B α . Mitogen-activated protein kinase (MAPK) is an essential member of the intracellular signaling protein network that mediates extracellular stimuli to intracellular responses.…”
Section: Resultsmentioning
confidence: 99%
“…found that CYP4A suppression by HET0016 (a selective CYP450 inhibitor) or siRNAs alleviates myocardial oxidative injury and apoptosis by activating the AKT signaling pathway 42 . Liu et al also discovered that the activated PI3K/AKT signaling pathway can reduce the level of cellular oxidative stress injury and inhibit the generation and secretion of various proin ammatory cytokines, thereby ameliorating the symptoms of chronic kidney disease 43,44 . Consistent with the aforementioned studies, our results con rmed that CYP4A11/20-HETE caused its deleterious effects on excessively increasing oxidative stress and inhibiting proliferation both in vitro and in a pregnant mouse model by decreasing the levels of phosphorylated PI3K and AKT.…”
Section: Discussionmentioning
confidence: 99%
“…NRG1β is expressed in the cardiac microvascular endothelium, and promotes the growth and survival of cardiac myocytes in culture through the activation of ErbB2 and ErbB4 receptor tyrosine kinases ( Fukazawa et al, 2003 ). On the one hand, NRG1 β could reduce circulating levels of proinflammatory cytokines in rats with sepsis, adjust diaphragmatic proinflammatory cytokine level, mitigate diaphragmatic oxidative injury, and lessen diaphragm cell apoptosis, improving the function of the diaphragm and playing a role in the protection of the diaphragm by activating the signalling of PI3K/Akt ( Liu et al, 2020 ). On the other hand, expression of NRG1 and recombinant NRG1β protects myocytes from anthracycline and β-adrenergic receptor-induced cell injury and death ( Zhao et al, 1998 ; Sawyer et al, 2002 ; Fukazawa et al, 2003 ; Kuramochi et al, 2004b ).…”
Section: Nrg1 With Cardiovascular Diseasesmentioning
confidence: 99%